Gender- and Age-Associated Differences in Bone Marrow Adipose Tissue and Bone Marrow Fat Unsaturation Throughout the Skeleton, Quantified Using Chemical Shift Encoding-Based Water–Fat MRI - Beekman, Kerensa M.; Regenboog, Martine; Nederveen, Aart J.; Bravenboer, Nathalie; den Heijer, Martin; Bisschop, Peter H.; Hollak, Carla E.; Akkerman, Erik M.; Maas, Mario (Frontiers in Endocrinology, 2022)
Bone marrow adipose tissue (BMAT) is a dynamic tissue which is associated with osteoporosis, bone metastasis and primary bone tumors. The aim of this study is to determine region-specific variation and age- and gender-specific differences in BMAT and BMAT composition in healthy subjects. In this cross-sectional study we included 40 healthy subjects (26 male: mean age 49 years, range 22-75 years; 14 female: mean age 50 years, range 29-71) and determined the bone marrow signal fat fraction and bone marrow unsaturation in the spine (C3-L5), pelvis, femora and tibiae using chemical shift encoding-based water-fat imaging (WFI) with multiple gradient echoes (mGRE). Regions of interest covered the individual vertebral bodies, pelvis and proximal epimetaphysis, diaphysis and distal epimetaphysis of the femur and tibia. Spinal fat fraction increased from cervical to lumbar vertebral bodies (Mean fat fraction (± SD or (IQR): cervical spine 0.37 ± 0.1; thoracic spine 0.41 ± 0.08. lumbar spine 0.46 ± 0.01; p<0.001). Femoral fat fraction increased from proximal to distal (proximal 0.78 ± 0.09; diaphysis 0.86 (0.15); distal 0.93 ± 0.02; p < 0.001), while within the tibia the fat fraction decreased from proximal to distal (proximal 0.92 ± 0.01; diaphysis 0.91 (0.02); distal 0.90 ± 0.01; p<0.001). In female subjects age was associated with fat fraction in the spine, pelvis and proximal femur (ρ=0.88 p<0.001; ρ=0.87 p<0.001; ρ=0.63 p=0.02; ρ=0.74 p<0.001, respectively), while in male subjects age was only associated with spinal fat fraction (ρ=0.40 p=0.04). fat fraction and unsaturation were negatively associated within the spine (r=-0.40 p=0.01), while in the extremities fat fraction and unsaturation were positively associated (distal femur: r=0.42 p=0.01; proximal tibia: r=0.47, p=0.002; distal tibia: r=0.35 p=0.03), both independent of age and gender. In conclusion, we confirm the distinct, age and gender dependent, distribution of BMAT throughout the human skeleton and we show that, contradicting previous animal studies, bone marrow unsaturation in human subjects is highest within the axial skeleton compared to the appendicular skeleton. Furthermore, we show that BMAT unsaturation was negatively correlated with BMAT within the spine, while in the appendicular skeleton, BMAT an BMAT unsaturation were positively associated.